2006
DOI: 10.1136/oem.2005.022293
|View full text |Cite
|
Sign up to set email alerts
|

Associations of SF-36 mental health functioning and work and family related factors with intentions to retire early among employees

Abstract: These findings highlight not only the importance of low mental health and unfavourable working conditions but also the simultaneous impact of conflicts between work and family to employees' intentions to retire early.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 29 publications
3
35
1
2
Order By: Relevance
“…One study indicated that older employees with longer time horizons and longer expectations of life have a preference to extend working life [136]. In addition, early dissatisfaction, been bought up in a problem family, dropping out of school or poor mental health earlier in life result in a greater risk for early retirement [132,137].…”
Section: Motivation and Work Satisfactionmentioning
confidence: 99%
“…One study indicated that older employees with longer time horizons and longer expectations of life have a preference to extend working life [136]. In addition, early dissatisfaction, been bought up in a problem family, dropping out of school or poor mental health earlier in life result in a greater risk for early retirement [132,137].…”
Section: Motivation and Work Satisfactionmentioning
confidence: 99%
“…Although the literature on the subject of retirement intention specifically is relatively limited, it has been shown repeatedly that adverse psychosocial workloads are associated with an increased wish for early retirement [1][2][3][4][5][6][7][8][9][10]. In order to identify which occupational psychosocial factors may be the most important in motivating people to continue working or the opposite, at least two conditions may play a major role: health status and economic necessity.…”
Section: Introductionmentioning
confidence: 99%
“…A versão reduzida de 36 itens tem sido amplamente utilizada na avaliação da qualidade de vida relacionada com a saúde em populações com ou sem doença (e.g. Atlantis, Chow, Kirby, & Singh, 2004;Harkonmaki, Rahkonen, Martikainen, Silventoinen, & Lahelma, 2006;Ilburg, Rasmussen, & Avlund, 2006;Myles, Viira, & Hunt, 2006). Numa iniciativa alargada de adaptação do instrumento foi criado o Projecto International Quality of Life Assessment (IQOLA) no qual participaram catorze países (Ware & Gandek, 1998 Em Portugal, este instrumento foi aplicado numa amostra de 930 mulheres grávidas e no puerpério (Ferreira 2000b) e numa amostra não representativa da população portuguesa constituída por 2358 indivíduos "saudáveis" e "com doença crónica", com idades entre os 16 e os 95 anos (Ribeiro, 2005).…”
Section: Amostraunclassified